Personal Characteristics and Nurses' Caring Behaviour - Veronika Hutabarat; Enie Novieastari; Kuntarti Kuntarti; Farida Murtiani (Universitas Muhammadiyah Semarang, 2022)
Caring behavior is a fundamental aspect of nurses in performing nursing care including professional attitudes, knowledge and skills that have an impact on nursing care and services and patient safety. Objective study to identify the relationship of personality characteristics with nurses caring behavior. Using a cross sectional design with a sample of 124 nurses working in the Jakarta Government Hospital. The research instrument consisted of nurse characteristics, nurse caring behavior, Core Self Evaluation (CSE) personality model characteristics and Dominance, Influence, Steadiness and Compliance (DISC) personality type characteristics. Characteristics of the CSE personality models have a moderate relationship and positive direction (p = 0, 0001, r = 0.496) with caring behavior, and the greatest correlation is self-efficacy (p = 0.0001, r = 0.528), and the lowest correlation is emotional stability (p = 0.0006, r = 0.243). While the DISC personality type and nurse characteristics have no relationship (p> 0.05). CSE personality model characteristics are related to nurses caring behaviour. While DISC personality type characteristics and nurse characteristics do not have a relationship with nurse caring behaviour. The factor that most influences caring behaviour is personality self-efficacy.